Environmental heterogeneity shapes the C and S cycling-associated microbial community in Haima's cold seeps - Chen, Yu; Dai, Tianjiao; Li, Niu; Li, Qiqi; Lyu, Yuanjiao; Di, Pengfei; Lyu, Lina; Zhang, Si; Li, Jie (Frontiers in Microbiology, 2023)
Environmental heterogeneity in cold seeps is usually reflected by different faunal aggregates. The sediment microbiome, especially the geochemical cycling-associated communities, sustains the ecosystem through chemosynthesis. To date, few studies have paid attention to the structuring and functioning of geochemical cycling-associated communities relating to environmental heterogeneity in different faunal aggregates of cold seeps. In this study, we profiled the microbial community of four faunal aggregates in the Haima cold seep, South China Sea. Through a combination of geochemical and meta-omics approaches, we have found that geochemical variables, such as sulfate and calcium, exhibited a significant variation between different aggregates, indicating changes in the methane flux. Anaerobic methanotrophic archaea (ANME), sulfate-reducing, and sulfide-oxidizing bacteria (SRB and SOB) dominated the microbial community but varied in composition among the four aggregates. The diversity of archaea and bacteria exhibited a strong correlation between sulfate, calcium, and silicate. Interspecies co-exclusion inferred by molecular ecological network analysis increased from non-seep to clam aggregates and peaked at the mussel aggregate. The networked geochemical cycling-associated species showed an obvious aggregate-specific distribution pattern. Notably, hydrocarbon oxidation and sulfate reduction by ANME and SRB produced carbonate and sulfide, driving the alkalization of the sediment environment, which may impact the microbial communities. Collectively, these results highlighted that geofluid and microbial metabolism together resulted in environmental heterogeneity, which shaped the C and S cycling-associated microbial community.